Do Eurozone Countries Cheat with their Budget Deficit Forecasts? - Andreas Stephan; Tilman Brück (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
We estimate the political economy determinants of budget deficit forecast errors. Since the adoption of the Stability Pact, Eurozone governments have manipulated forecasts before elections. The political orientation and the institutional design of governments also affects the quality of forecasts.
Keywords: H87; E62; C23; H62; C53; 330; fiscal policy; budget deficit; forecast error; electoral cycles; Haushaltsdefizit; Prognose; Staatliche Information; Politischer Konjunkturzyklus; EU-Stabilitätspakt; Deutschland